Optimasi Elektroda Pada Sistem Pembangkit Plasma Non Termik untuk Meningkatkan Kuantitas Benih Mangrove - Azam, Much.; Hidayanto, Eko (BERKALA FISIKA, 2006)
The Mangrove is the tropics  nature resources that has two aspects, economics and ecology. This plant can be  iradiated   by the corona discharge. It is need to radiate mangrove seed with nitrogen and analize it’s  growt.  For that have need optimations of the electrode on the non thermics plasma generator system  in order to get the effective and the efficient radiations.  The steps of the research are : analize system, make a prototype, test the prototype with simulations, compare  the simulations result with the experiment result and analize the results. From the research can get conclution that: 1) had been succes to make prototype of  the mangrove plant reproduction  system by the corona discharge plasma technology with the point-plant electrode, 2) the simulations result show that  electrical fields shall increase if the distance from electrode has been  decreases, or the voltage of electrode has been  incresed, or the distance among electrode has been decreased  or  the value of the electrode radius.has been opotimum, 3) the result of simulations show that the current density  shall  decrease if distance among electrode has been decreased, 4)for the same distance electrode, the electricel fields of the experiment results  is bigger than the simulations result, because the value of permeability and permittivity medium on the simulation is using the  value of    the vaccum  space.     Key words : the non thermics plasma, iradition, Mangrove